Source attribution and quantification of atmospheric nickel concentrations in an industrial area in the United Kingdom (UK). (15th January 2022) - Font, Anna; Tremper, Anja H.; Priestman, Max; Kelly, Frank J.; Canonaco, Francesco; Prévôt, André S.H.; Green, David C.
Abstract: Pontardawe in South Wales, United Kingdom (UK), consistently has the highest concentrations of nickel (Ni) in PM10 in the UK and repeatedly breaches the 20 ng m −3 annual mean EU target value. Several local industries use Ni in their processes. To assist policy makers and regulators in quantifying the relative Ni contributions of these industries and developing appropriate emission reduction approaches, the hourly concentrations of 23 elements were measured using X-ray fluorescence alongside meteorological variables and black carbon during a four-week campaign in November–December 2015. Concentrations of Ni ranged between 0 and 2480 ng m −3 as hourly means. Positive Matrix Factorization (PMF) was used to identify sources contributing to measured elements. Cluster analysis of bivariate polar plots of those factors containing Ni in their profile was further used to quantify the industrial processes contributing to ambient PM10 concentrations. Two sources were identified to contribute to Ni concentrations, stainless-steel (which contributed to 10% of the Ni burden) and the Ni refinery (contributing 90%). From the stainless-steel process, melting activities were responsible for 66% of the stainless-steel factor contribution. Graphical abstract: Image 1 Highlights: Pontardawe Tawe Terrace is the site with the highest Ni concentration in the UK. A four-week campaign measured 23 high-time resolved elements in PM10 including Ni. Campaign mean Ni was 19.6 ng m −3 but showed large variability (0–2480 ng m −3 ). 90% of the total Ni in PM10 was attributed to the nickel refinery. Abstract : Atmospheric nickel concentrations in PM10 in an industrial area in the UK: concentrations and sources.